THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL SELF-EFFICACY ON FINANCIAL MANAGEMENT BEHAVIOR OF GENERATION Z IN MEDAN CITY - Farida Syah Damanik; Nurwani Nurwani; Ahmad Perdana Indra (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to analyze the influence of financial literacy and financial self-efficacy on financial management behavior among Generation Z in Medan City, both partially and simultaneously. The population in this study was all Generation Z in Medan City. The study used a quantitative approach with data collection techniques through distributing questionnaires. A sample of 100 respondents was selected using an accidental sampling technique. Data analysis was carried out using multiple linear regression through stages of validity, reliability, classical assumptions, t-test, F-test, and coefficient of determination. The results showed that financial literacy and financial self-efficacy have a positive and significant effect on financial management behavior, both partially and simultaneously. These findings indicate that increasing financial literacy and an individual's self-confidence in their ability to manage finances play an important role in shaping better financial behavior in the younger generation.